SCIENTIFIC AND THEORETICAL ANALYSIS OF THE PHENOMENON OF CHARITY AND SPONSORSHIP (ON THE EXAMPLE OF THE EMIRS OF BUKHARA) (Scientific journal of the Fergana State University, 2023)
The scientific-theoretical analysis of the role and importance of the values of charity and sponsorship in the history of our country, its formation stages, as well as the extent to which the Emirs of Bukhara, who ruled in the first half of the mid-18th century, paid attention to such human qualities as charity, sponsorship and patronage, and the role of has been illustrated in the article. The charity and sponsorship carried out by the emirs of Bukhara in other regions of the Russian Empire has also been shown.